EVALUATION OF BC 1 F 1 PLANTS DEVELOPED BY MAS FOR BLB RESISTANCE IN RICE - and D. SRINIVASA CHARY, B.EDUKONDALU , V. GOURI SHANKAR P. REVATHI, D. SAIDA NAIK (The Journal of Research, PJTSAU, 2021)
Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is the most destructive disease affecting the rice production worldwide. RP 5933-1-19-2 R is a high yielding genotype but susceptible to rice bacterial leaf blight. In this study, two major bacterial leaf blight (BLB) resistance genes Xa21 and xa13 were introgressed into RP 5933-1-19-2 R throughmarker-assisted backcross breeding BC1F1 generation during Kharif, 2018 to Rabi, 2019-20 at ICAR-IIRR, Rajendranagar. Improved Samba Mahsuri (possessing Xa21 and xa13) was used as donor parent. Two PCR based functional markers pTA248 and xa13 prom were used for foreground selection to derive the improved lines for BLB. Fifteen out of the 76 BC1F1 plants were identified with both genes (Xa21 and xa13) in heterozygous condition. On the basis of agronomic traits and resistance to BLB, three promising plants, BC1F1-11, BC1F1-16 and BC1F1-25 were selected for further generations.